Cytotoxicity of catechol towards human glioblastoma cells via superoxide and reactive quinones generation Citotoxicidade do catecol para células de glioblastoma humano via geração de superóxido e quinonas reativas - Marco Roberto Guimarães Pereira; Elineusa Silva de Oliveira; Flávio Augusto Guerreiro Aragão de Villar; Maria Socorro Grangeiro; Júlia Fonseca; Ana Rita Silva; Maria de Fátima Dias Costa; Sílvia Lima Costa; Ramon dos Santos El-Bachá (Sociedade Brasileira de Patologia Clínica, 2004)
It is known that the exposure to benzene in the petroleum industry causes lympho-haematopoietic cancer among workers. However, there is little data concerning the toxicity of benzene to the central nervous system. Benzene easily penetrates the brain where it is metabolized to catechol. Since catechol autoxidizes in physiological phosphate buffer, we hypothesized that it could be toxic towards glial cells due to the generation of reactive oxygen species and quinones. In this work we studied the cytotoxic properties of catechol towards human glioblastoma cells. We found that catechol was toxic towards these cells after 72 hours and this toxicity was related to the formation of quinones. Catechol at 230µM killed 50% of cells. The catechol-induced cytotoxicity was prevented by the addition of 100U superoxide dismutase, which also inhibited the formation of quinones. These data suggest that catechol induces cytotoxicity via the extracellular generation of superoxide and quinones. Sabe-se que a exposição de trabalhadores ao benzeno na indústria petrolífera é uma causa de câncer do sistema linfo-hematopoiético. Pouco se sabe, contudo, a respeito da toxicidade do benzeno no sistema nervoso central. O benzeno penetra facilmente no cérebro, onde é metabolizado a catecol. Como o catecol se auto-oxida em tampão fosfato no pH fisiológico, supôs-se que esse composto poderia ser tóxico para células gliais por gerar espécies reativas do oxigênio e quinonas. Nesse trabalho estudou-se a citotoxicidade do catecol para células de glioblastoma humano. O catecol foi tóxico após 72 horas e essa toxicidade relacionou-se com a formação de quinonas. O catecol a 230mM matou metade das células em cultura. A toxicidade do catecol e a produção de quinonas foram inibidas por 100U de superóxido dismutase. Esses dados sugerem que a toxicidade induzida pelo catecol deve-se à produção extracelular de superóxido e quinonas reativas.